Examining gender differences in ball reversal and paint touch usage in NCAA division I basketball games - Karamousalidis, G.; Agathokleous, M.; Tsimpouris, I.; Michailidis, I.; Foteinakis, P. (Journal of Physical Education and Sport, 2025)
In recent years, there has been a growing focus on analyzing the factors that improve offensive efficiency in basketball. This study compared men's and women's NCAA Division I basketball teams by examining ball reversals, paint touches, and the use of passing and dribbling per possession. A total of 7,496 offensive possessions from 46 regular-season games during the 2023-24 season were analyzed using Sports Count STA. Statistical analysis was performed using SPSS 29. Descriptive statistics were first computed, followed by independent samples t-tests, binary logistic regression, and chi-square (X²) crosstabulation analysis to examine differences across variables. The significance level was set at p < .05. The results showed that men's teams had a higher frequency of passes per possession, while women's teams relied more on dribbling. Winning teams demonstrated more frequent passing per possession and achieved greater offensive efficiency. Notably, possessions that included at least one paint touch resulted in the highest offensive efficiency (i.e., points per possession, ppp) in both men's and women's games. Additionally, multiple ball reversals combined with an inside-focused offense were associated with increased offensive effectiveness. In conclusion, increased passing, a focus on paint touches often combined with ball reversals, minimizing one-dimensional individual actions such as excessive dribbling, and effective fast-break execution are all associated with higher offensive efficiency, regardless of gender. These findings provide valuable insights and highlight potential directions for future research on offensive tactical patterns. Future research could focus on these tactical variables in relation to specific game moments, score fluctuations, or the competitiveness of the match.